Numerical Simulation of the Interaction between Slender Body Vortices and a Fin - A. Omar, Ashraf; Kim, Chongam; Rho, Oh Hyun (Universiti Putra Malaysia Press, 2001)
The interaction between slender body vortices and a single fin located down the axis of the body is investigated numerically for angle of attack of 30 deg. and Reynolds number of 6000. The present research includes a parametric study on the effects of fin axial and azimuthal positions on the development of the vortex system. A numerical method based on the pseudo-compressibility is used for solving the three-dimensional incompressible Navier-Stokes equations using Lower-Upper Symmetric Gauss-Seidel implicit scheme. The numerical results show that the vortices remain very coherent and attached to the body until they reach the fin section where they become less coherent and begin to separate from the body. Also, the result shows that the fin location does not affect the upstream development of the vortices but it does affect the location at which the vortices separate from the body. The effect of azimuthal fin positions was also investigated. As azimuthal angle of the fin increased, the size of the vortex on the port side decreased, but the starboard side vortex grew in size and moved across the leeward ray to the port side. The computed results are found to agree well with the experimental data.